Berberine protects against light-induced photoreceptor degeneration in the mouse retina. (April 2016) - Song, Delu; Song, Jiantao; Wang, Chenguang; Li, Yafeng; Dunaief, Joshua L.
Abstract: Oxidative stress and inflammation play key roles in the light damage (LD) model of photoreceptor degeneration, as well as in age-related macular degeneration (AMD). We sought to investigate whether Berberine (BBR), an antioxidant herb extract, would protect the retina against light-induced degeneration. To accomplish this, Balb/c mice were treated with BBR or PBS via gavage for 7 days, and then were placed in constant cool white light-emitting diode (LED) light (10, 000 lux) for 4 h. Retinal function and degeneration were evaluated by histology, electroretinography (ERG) and optical coherence tomography (OCT) at 7d after LD. Additionally, mRNA levels of cell-type specific, antioxidant, and inflammatory genes were compared 7d after LD. Photoreceptor DNA fragmentation was assessed via the terminal deoxynucleotidyl transferase dUTP nick end-labeling (TUNEL) assay. LD resulted in substantial photoreceptor-specific cell death. Histological analysis using plastic sections showed dosing with BBR preserved photoreceptors. The ERG analysis demonstrated functional protection by BBR in rod-b, -a, and cone-b waves. In OCT images, mice receiving PBS showed severe thinning and disorganization of the photoreceptor layer 7 days after LD, whereas mice treated with BBR had significantly less thinning and disorganization. Consistent with OCT results, the mRNA levels of Rho in the NSR, and Rpe65 and Mct3 in the RPE, were significantly higher in mice treated with BBR. The numbers of TUNEL-positive photoreceptors were significantly decreased in BBR-treated mice. The retinal mRNA levels of oxidative stress genes, the number of microglia/macrophages, and the malondialdehyde (MDA) immunolabeling were significantly lower in BBR-treated mice compared to controls 48 h after LD, which indicates oxidative stress was reduced by BBR in light-damaged eyes. In conclusion, systemic BBR is protective against light-induced retinal degeneration associated with diminished oxidative stress in the retina. These results suggest that BBR may be protective against retinal diseases involving oxidative stress. Highlights: BBR protects photoreceptors against light damage. BBR diminishes light-induced retinal antioxidant gene upregulation. BBR diminishes light-induced inflammatory gene upregulation in the retina.